Antibacterial activity of novel linear polyamines against Staphylococcus aureus - Douglas, Edward J. A.; Alkhzem, Abdulaziz H.; Wonfor, Toska; Li, Shuxian; Woodman, Timothy J.; Blagbrough, Ian S.; Laabei, Maisem (Frontiers in Microbiology, 2022)
New therapeutic options are urgently required for the treatment of Staphylococcus aureus infections. Accordingly, we sought to exploit the vulnerability of S. aureus to naturally occurring polyamines. We have developed and tested the anti-staphylococcal activity of three novel linear polyamines based on spermine and norspermine. Using a panel of genetically distinct and clinically relevant multidrug resistant S. aureus isolates, including the polyamine resistant USA300 strain LAC, compound AHA-1394 showed a greater than 128-fold increase in inhibition against specific S. aureus strains compared to the most active natural polyamine. Furthermore, we show that AHA-1394 has superior biofilm prevention and biofilm dispersal properties compared to natural polyamines while maintaining minimal toxicity towards human HepG2 cells. We examined the potential of S. aureus to gain resistance to AHA-1394 following in vitro serial passage. Whole genome sequencing of two stable resistant mutants identified a gain of function mutation (S337L) in the phosphatidylglycerol lysyltransferase mprF gene. Inactivation of mutant mprF confirmed the importance of this allele to AHA-1394 resistance. Importantly, AHA-1394 resistant mutants showed a marked decrease in relative fitness and increased generation time. Intriguingly, mprF::S337L did not contribute to altered surface charge and the exact contribution to AHA-1394 resistance is not clear. Lastly, we show that AHA-1394 displays a particular proclivity for antibiotic potentiation, restoring sensitivity of MRSA and VRSA isolates to oxacillin and vancomycin. Together this study shows that polyamine derivatives are impressive drug candidates that warrant further investigation.